Perilaku Penggunaan Dompet Digital pada Generasi Z di Bogor - Octavian, Henry Sumurung; Soedargo, Bayu P. (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Digital payments have now become a new habit for the most consumer along with the development of non-cash payment innovations. There has been an increase in the use (intensity and value) of digital money in recent years along with the pandemic in the effort of touch-less transactions. Consumer behavior with a demographic background, the age group born in 1997-2021, known as generation Z is the digital native generation to be interesting because they will become a big market in the years ahead. The formulation of the research problem is that service quality, perceived convenience, perceived benefits, and promotions have a positive influence on the use of digital money. The purpose of this study is to find out how much interest and intensity in using digital wallets are among generation Z and to find out the relationship between variables both internal and external to consumers in the use of digital wallets. Research will be conducted using research methods. Primary data will be taken using an e-form survey on generation z respondents in several schools and campuses in the city of Bogor. The collected data will be processed and analyzed using the method of description, cross tabulation, and analytical approach with Technology Acceptance Model (TAM). The results of the study show support for the research hypothesis and also previous research related to the use of digital wallets, except for an insignificant relationship of perceived ease of to use (PEOU) on behavioral intention (BI). From the behavioral patterns of digital wallet users, researchers recommend to explore the factors that exist in each variable Keywords: Financial Technology, Payment Behavior, Digital Wallet, Generation Z, Technology Acceptance Model